THE ROLE OF STORIES IN THE WORKS OF ALISHER NAVOY (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This scientific article focuses on the stories about Leyli and Majnun, who took place in the works of Navoi. The works of Alisher Navoi “Mahbub ul-qulub”, “Lison ut-Tayr” and “Saddi Iskandari” were taken as the basis for the research of the topic. In the article, artistic landscapes about Layla and Majnun are drawn to the analysis.